Ratcheting up Paris - Humberto G. Llavador; John E. Roemer; Thomas Stoerk (National Bank of Belgium, 2026)
The Paris Agreement is designed to increase climate ambition gradually through a process of ratcheting up. What is the plausible endpoint of this process? We develop a tractable integrated assessment model in which countries interact through a decentralized general equilibrium and negotiate unanimously over a global carbon budget, with all mitigation implemented via a global carbon price. We prove existence and uniqueness of a unanimous international agreement on global emissions, in which carbon pricing revenues are redistributed across countries in proportion to marginal climate damages. In a quantitative application for 154 countries, the resulting equilibrium limits global mean surface temperature change to 1.51C, at a carbon price of 320 USD/tCO2. The associated international transfers of carbon pricing revenue are progressive toward lower-income countries and amount to about 0.8% of global GDP annually - an order of magnitude larger than the Paris Agreement's climate finance target.
Keywords: Q54; Q56; Q58; F35; F53; 330; Paris Agreement; climate policy; international environmental agreement; climate economics